A study and pragmatic proposal on the communication of human involvement in Brazilian computing research - Carvalho, Luiz Paulo; Rios da Hora Rodrigues, Kamila; Santoro, Flávia Maria; Oliveira, Jonice (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Research involving people requires ethical or moral scrutiny, such as specific resolutions. Compared to a few decades ago, significantly more research in computing involves people aligned with a moral outlook and oriented toward more significant appreciation for this topic. Based on research with both a secondary and pragmatic approach, we present a transformative intention to advance the ethical and moral scenario related to the involvement of people in computing research and, additionally, improve scientific communications accordingly. Secondary research indicates that the scenario is chaotic and deficient, with several erroneous or problematic occurrences in research practice and communication. In the first consolidated effort, we bring a communication artifact, a textual framework, for better quality when reporting data on people's involvement in research. In conclusion, despite the adverse scenario perceived in this study, which we conjecture results from ignorance and poor education on the subject, we forward a proposal to help, in practice, a moral advance to Brazilian science and computing, emphasizing the context of Human-Computer Interaction.